Chemical and physical characteristics of cocopeat-based media mixtures and their effects on the growth and development of Celosia cristata - Awang, Yahya; Shaharom, Anieza Shazmi; Mohamad, Rosli; Selamat, Ahmad (Science Publications, 2009)
Problem statement: Cocopeat is considered as a good growing media component with acceptable pH, electrical conductivity and other chemical attributes but it has been recognized to have high water holding capacity which causes poor air-water relationship, leading to low aeration within the medium, thus affecting the oxygen diffusion to the roots. Incorporation of coarser materials into cocopeat could improve the aeration status of the media. Approach: Selected chemical and physical characteristics of five types of growing media comprising of (v/v) 100% cocopeat, 70% cocopeat: 30% burnt rice hull, 70% cocopeat: 30% perlite, 70% cocopeat: 30% kenaf core fiber and 40% cocopeat: 60% kenaf core fiber were determined and their suitability as growing media was tested using Celosia cristata. Data on pH, Electrical Conductivity (EC) and various aspects of air-water relationships of the media, as well on growth and flowering of test plant and leaf nutrient contents were collected. Results: Initial pH for 100% cocopeat and 70% cocopeat: 30% kenaf core fiber was higher than the other media but the values were eventually similar by the end of the study. The bulk density and EC of media containing burnt rice hull was markedly higher than the other media (0.12 g cm3 and 0.48 mS cm-1, respectively). Media comprising of 70% cocopeat: 30% burnt rice hull and 70% cocopeat: 30% perlite contained higher air content. The former held the highest volume of available water. Incorporation of burnt rice hull and perlite into cocopeat increased water absorption ability of the media which reached saturation earlier than the other media. Addition of burnt rice hull (30%), perlite (30%) and kenaf core fiber (30%) to cocopeat elevated the Air-Filled Porosity (AFP) of the media. The growth and flowering of Celosia cristata were the greatest when grown in a mixture of 70% cocopeat: 30% burnt rice hull and perhaps linked with a good balance in the aeration and moisture relationship of the media. Conclusion: Results of this study indicated that certain chemical and physical properties of cocopeat can be improved through incorporation of burnt rice hull and its positive effect was clearly reflected in the growth and development of Celosia cristata.